Development of composite hybridization of kenaf fibre and x-ray film for aerospace ballistic impact applications - Rayney Azmi, Ahmad Mustafa (2018)
During flight, aerospace structures are often exposed to high velocity impacts with both hard and soft or deformable objects. These objects include metal pieces or fragments, stone debris, birds, hailstones, and tyre rubber. Therefore, in the design of aerospace structures, engineers are required to implement composite structures that are able to withstand this type of impact. This thesis aims at developing a novel hybrid composite material based on kenaf fibre and x-ray films and at analysing the obtained materials with regard to their mechanical properties, as well as high velocity impact and compression after impact behaviour, with a view to determining their potential to compete with existing high velocity impact resistant materials, which are presently used to fabricate the insert plates of bulletproof vests. The kenaf fibre used to reinforce the composites was treated with NaOH solution, and, for comparison purposes, composites were prepared with both treated and untreated kenaf fibre. Similarly, the x-ray films were punctured to improve adhesion between the layers and composites were fabricated with both punctured and unpunctured x-ray films. The materials were fabricated using the conventional hand lay-up method, with 7 layers arranged according to different configurations. The optimum configuration was then chosen – judging by the mechanical characteristics obtained – and improved. The new configuration was then used to fabricate a series of samples to be tested with regard to their behaviour to high velocity impact. A single stage gas gun was used for the tests, and the analysed variables were the pressure of the gas gun – which influences the velocity of the bullets – and the type of the bullets. The bullet types used were: blunt or flat bullets, hemispherical bullets and conical or chisel-pointed bullets. The pressure for the gas gun was varied as follows: 20 bar, 30 bar, 40 bar and 50 bar. The tests revealed that the hemispherical bullets penetrated the specimens the most easily, followed by the conical ones and lastly by the blunt bullets. The experiments demonstrated that the developed composite was impact resistant and managed to absorb more than 130 J of energy at a bullet speed of up to 230 m/s.